A Bibliometric Analysis of Biodiversity Reporting in Accounting - Drae BENT; Elisabete VIEIRA; Mara MADALENO (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:Over the years, biodiversity reporting has received increasing interest due to its importance in understanding our impact on the environment and biodiversity loss. The purpose of this study is to present a bibliometric analysis of emerging and relevant publications on biodiversity reporting in accounting.Methodology:This study synthesizes previous works of literature on biodiversity reporting in accounting using the bibliometric analysis approach. The data covering the period of 1996 - 2021 was collected using the Scopus database to ascertain the publications, countries, authors, keywords, and journals that have contributed to the body of knowledge. VOSviewer software was used as a visual output for the relevant data points and interpretation.Findings:The findings showed that biodiversity reporting in accounting is still an emerging topic, and there are continued maturing interests.Implication:This paper concludes by highlighting the main trends in research on biodiversity reporting and offers potential opportunities for future research in this field.